KAJIAN SIMBOLIK PADA TRADISI PUTER KAYUN - Wisri Wisri; Nurul Imaroh (LP2M Universitas Ibrahimy, 2021)
In social life, we are often faced with ingrained cultures or traditions. Culture or tradition seems to be a benchmark for a society to be in harmony with other people and their environment if they have obeyed and maintained that culture. The type and research strategy used by the researcher in this study is descriptive qualitative. It is a study that leads to a detailed and in-depth description of the real condition of what actually happened in the field of study. The results of the study found that the Puter Kayun traditional ceremony in Boyolangu Village, Giri District, Banyuwangi Regency contained religious, spiritual and social meanings. This can be seen from the interaction of the community and the symbols used in the implementation of this traditional ceremony. For example, the meaning of the implementation of Puter Kayun is a form of keeping a promise to Ki Buyut Jakso to trace his struggle from Boyolangu Village to Watu Dodol beach, besides it is carried out as a form of gratitude to Allah SWT. Puter Kayun has three accompanying procession models, they are Kopat Sewu, Selametan Deso and the Kebo-keboan procession. The meanings contained in the Puter Kayun tradition as well as the symbols used in the implementation of the Puter Kayun tradition cannot be separated from the society's argument that an object usually has certain values.